The latitudinal speciation gradient in freshwater fishes: Higher speciation across assemblages at higher latitudes in the northern hemisphere - Juliana Herrera-Pérez; Juan Carvajal-Quintero; Axel Arango; Daniel Valencia-Rodríguez; Ana Berenice García-Andrade; Pablo Tedesco; Fabricio Villalobos (PLoS ONE, 2026)
Speciation rates are a key driver of diversity patterns and are often used to explain the latitudinal diversity gradient (LDG). However, latitudinal variation in speciation rates at both assemblage and species levels remains poorly explored in freshwater fishes. This highlights a gap in understanding the mechanisms driving geographic biodiversity gradients in freshwater fishes. Here, we investigated the latitudinal speciation gradient in freshwater fishes, using a comprehensive database of freshwater fish distributions and phylogenetic relationships of Actinopterygian fishes at the global scale. We estimated speciation rates using three metrics (BAMM, DR, and ClaDS) and evaluated the latitudinal speciation gradient through spatial and phylogenetic regressions at assemblage and species levels. Finally, we analyzed those patterns based on the species assemblage’s phylogenetic diversity and structure. Our results show that areas and species with the highest speciation rates were in the tropics. However, the general assemblage pattern revealed a positive relationship between absolute latitude and speciation rates. This relationship is generally absent in tropical regions below 24.39° and became significant only at higher latitudes, particularly in the Northern Hemisphere. We did not find a significant relationship at the species level, mainly due to the strong influence of hyper-diverse groups like Cichliformes. Species-level findings showed the contribution of particular lineages to the speciation gradient as a whole, while the assemblage-level results emphasize the high speciation rates across the Northern Hemisphere, especially North America, potentially resulting from environmental filtering and dispersal events consistent with glaciation dynamics in the Pleistocene.